上下顎手術における骨延長術の役割 - 森, 良之; 菅野, 勇樹 (日本口腔外科学会雑誌, 2013)
Recently, distraction osteogenesis （ DOG） has been used to various deformities of oral and maxillofacial area, because it is effective for not only increasing bone length but also the volume of surrounding soft tissues, including skins, muscles, vessels, and nerves. In patients who have skeletal reversed occlusion caused by maxillary hypoplasia with cleft lip and palate, we perform 2-stage surgery, which is combining maxillary advancement by distraction technique before mandibular setback surgery, in order to extend the palatal scar tissue at the same time, and they get stable occlusion. This technique can be applied to treatment for hemifacial microsomia（ HFM） patients with soft tissue turgor in adult as combining mandibular advancement by distraction technique before maxillary translation surgery. Additionally, DOG is useful option to secondary lengthening of the reconstructed mandible for obtaining improvement of maxillamandibular relation, and soft tissue expansion for making the space of mandibular reconstruction in the patients with contracture of oral tissue after tumor resection. However, especially in patients treated with radiation, they have encountered several complications such as infection, failure of bone formation, and skin breakdown, therefore, we should consider the therapeutic indication of DOG on patients carefully.